Nonmyopic Strategic Behavior in the MDP Planning Procedure - Truchon, Michel (Econometrica, 1984)
This paper addresses the question of nonmyopic strategic behavior in an MDP planning procedure which is terminated when the rate of adjustment in the quantity of the public good is below some prespecified threshold. The problem is formulated as a dynamic game in which utility functions are additively separable. It is shown that the game possesses perfect Nash equilibria whose outcomes are Pareto optima. Moreover, any individually rational Pareto optimum can be attained through one of these Nash equilibria. Strategies in these equilibria involve a rate of revision in the quantity of the public good that is equal to the threshold level and insures monotonic convergence of the procedure in finite time.